HUBUNGAN PENGETAHUAN, SIKAP SISWA TENTANGBAHAYA NARKOBA DAN PERAN KELUARGA TERHADAPUPAYA PENCEGAHAN NARKOBA (STUDI PENELITIAN DI SMP AGUS SALIM SEMARANG) - Yesi Ratnasari (Jurnal Kesehatan Masyarakat Indonesia, 2015)
Background: Increase in drug case in ever-increasing in teenagers, especially during theadolescent age of junior high school and high school, then drug prevention efforts need to be made Factors influencing drug abuse in teens is a teen's knowledge and the role of the family. Therefore it was done about the correlation of knowledge, the student's attitude about drugs and drug prevention efforts.. Objective: Knowing the correlation between knowledge, attitude of students about drugs and the role of the family with respect to drug prevention efforts. Methods: The type of research used is explanatory research with cross sectional .Popu lation in this study as many as 161 students with a large sample of 62 respondents. Independent variable was drug prevention efforts and dependent variable is the knowledge, the attitude of the students about drugs, the role of the family and prevention efforts. Analysis using pearson product moment correlation. Results: As much as 64.5%) of respondents (have enough knowledge, as many of the respondents who had not supported the attitude about the dangers of drugs as much as (61,3%) respondents have the role of the family do not support as many (53.2%) and respondents who have as much good prevention efforts (51.6 percent). Conclusion: There was a correlation with the family's role in drug prevention efforts. variables therewhere no correlation knowledge and attitudinal with drug prevention efforts.